Probability theory, fourier transform and central limit theorem - Sorokin, Yegor (Kansas State University, 2009)
In this report we present the main concepts of probability theory: sample spaces, events, random variables, distributions, independence, central limit theorem. Most of the material may be found in the notes of Bass. The work is motivated by wide range of applications of probability theory in quantitative finance.
Keywords: probability; fourier transform; central limit; Mathematics (0405)